A New Approach to Scientific-Research Paper Evaluation - Bjelobaba, Goran; Stefanović, Hana; Savić, Ana; Stefanović, Nedeljko; Popović, Nikola (E-business technologies conference proceedings, 2021)
Unreviewed sources such as https://arxiv.org [1] have an advantage over reviewed ones, which reflects in the immediate availability of the former to the reader, whereas in the case of the latter, reviewed sources, it takes six months on average from the submission of a paper to the journal to its publication (in case the paper has been accepted). Reviewed papers, however, have obvious advantages that reviewing brings with itself. In the paper, a solution which should unite into one the good characteristics of both approaches is offered.